Hygric Behavior of Viticulture By-Product Composites for Building Insulation - Badouard, Céline; Maalouf, Chadi; Bliard, Christophe; Polidori, Guillaume; Bogard, Fabien (Materials, 2022)
One possible approach to reducing the environmental impacts associated with the building sector is the development and use of bio-based building materials. The objective of this study is to determine the water properties of bio-based insulation materials, derived from winegrowing co-products, which promote energy efficiency. The water performance of these new bio-based materials is based on the measurement of the moisture buffer value, the sorption isotherm, and the water vapor permeability. Four by-products are analyzed: stalks, grape pomace, crushed stalks, and skins; they are combined with a potato starch binder. The performance of these composites is compared to two other bio-based composites (hemp/starch and beet pulp/starch). The stalk/starch composite can be classified as a hygroscopic and breathable material with excellent moisture retention capacity.
Keywords: agromaterials; bio-based composite; hygric properties; hygrothermal performance; renewable raw sources